Social Connectedness in the Transition to Retirement Among Civil Servants: A Crosssectional Study in Yogyakarta, Indonesia - Indonesia, Tanah Cinta; Mulyani, Sri; Warsini, Sri (Universitas Negeri Semarang, 2025)
Background: Retirement is a transitional phase that affects various life aspects, including social relationships. Many civil servants feel socially unprepared, leading to reduced interactions, increased isolation, loneliness, and depressive symptoms. This highlights the need for social readiness to support retirees' well-being. Therefore, this study describes the social relationship readiness of prospective retired civil servants in the Special Region of Yogyakarta, Indonesia. Methods: A descriptive quantitative study with a cross-sectional design was conducted online via WhatsApp from November to December 2024, involving 171 prospective civil servant retirees who participated in the retirement preparation program organized by the Regional Civil Service Agency, using a consecutive sampling technique. The instrument used was the civil servant retirement readiness questionnaire by Mardova, which had been modified. Data analysis included univariate and bivariate analysis (Spearman’s rho, Chi-square, and Fisher’s exact test). Results: Most respondents (60.2%) were categorized as